2000
DOI: 10.1021/ol006491+
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Conjugated Chromophores:  Synthesis of iso-Polydiacetylenes with Donor/Acceptor Substitution

Abstract: The iterative construction of cross-conjugated donor (D), acceptor (A), and donor-acceptor (D-A) substituted iso-polydiacetylene (iso-PDA) oligomers has been achieved utilizing palladium-catalyzed cross-coupling techniques. Structure-property relationships for these compounds have been analyzed for cross-conjugated pi-electronic communication as a result of contributions from donor, acceptor, or donor-acceptor functionalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Such push-pull functionalization is a wellestablished mode for dictating the electronic characteristics and molecular hyperpolarizabilities for various linearly conjugated molecules [5]. Our work [13], and that of others [7] [14] [15], has suggested that D/A-substitution can cause notable changes in the electronic-absorption behavior of cross-conjugated oligomers as well.…”
mentioning
confidence: 58%
“…Such push-pull functionalization is a wellestablished mode for dictating the electronic characteristics and molecular hyperpolarizabilities for various linearly conjugated molecules [5]. Our work [13], and that of others [7] [14] [15], has suggested that D/A-substitution can cause notable changes in the electronic-absorption behavior of cross-conjugated oligomers as well.…”
mentioning
confidence: 58%
“…69 Evidence for intramolecular charge-transfer via cross conjugation came from UV-vis spectroscopy, which showed that D-A monomer 74a has a lower energy absorption tail that extends out beyond 450 nm, whereas 72a and 73a were transparent beyond about 425 nm. It was concluded, however, that charge-transfer mediated by the enyne framework was not present in the D-A dimer (74b) and trimer (74c).…”
Section: Iso-polydiacetylenesmentioning
confidence: 99%
“…Multiple conduction pathways in different dimensions are accessible by using cross-conjugated compounds 2022,29,30. Electron-donor and -acceptor moieties are frequently incorporated into cross-conjugated structures to improve the dimensionality of electronic communication 4,5,10,22,27,3640. Judicial placement of the donor and acceptor groups allows spatial separation of the HOMO and LUMO, as revealed by quantum-mechanical calculations.…”
Section: Introductionmentioning
confidence: 99%